How effective is microfinance in reaching the poorest? Empirical evidence on programme outreach in rural Pakistan - Ghalib, Asad K. (Journal of Business Economics and Management, 2013)
Microfinance has emerged on the global scale as a key strategy to reduce poverty and promote development. Most literature however, tends to concentrate on breadth as opposed to depth of programme outreach. This paper is based on a primary household survey of 1,132 respondents in the Punjab Province of Pakistan to assess which category of the poor is being served by microfinance institutions: are they the very poor, middle poor or less poor ones? In order to make comparisons, borrower (treatment) and non-borrower (control) households are ranked by poverty scores generated by employing Principal Component Analysis. The study reveals that the depth of poverty outreach is significantly lower than what has been claimed by lenders. The paper reflects on policy implications to enhance depth (as opposed to breadth) of outreach to address the needs of the ‘poorest of the poor’ in order to contribute meaningfully and effectively towards combating poverty.